BUDAYA KEWARGANEGARAAN, PRAKTEK KEWARGANEGARAAN DAN PENDIDIKAN UNTUK KEWARGANEGARAAN DEMOKRATIS - Kurniati, Pat; Putra, Haris Maiza; Komara, Lilis Sari; Wibianika, Handrian; Setiansyah, Reni (P2M STKIP Siliwangi, 2021)
Citizenship cultire is a virtue that includes activie citizen involvement, equality or egalitarian relation, mutual trust andÂ Â  tolerance, cooperative life, solidarity, abd community spirit. The concept of civic culture or Pancasila for Indonesia is closely related to the development of democratic civil society or Pancasila civil society. Citizenship Education has and is in line with the three main functions of civic education as a vehicle for the development of democratic citizens, namely developing civic intelligence, fostering civic responsibility, and encouraging civic participation. Three competencies of citizens This is also in line with the three components of good citizenship education, namely civic knowledge, civic skills, and civic disposisions. Citizens who have knowledge of citizenship will be smart citizens, participatory citizens, while citizens who have citizenship characters will be responsible citizens. Citizenship eduction must be designed, implemented and evaluated in the context of developing civic intelligence, which then radiates and crystallizes into civic civilization (civicvirtues/civility). This is a provision for every citizen to consciously carry out civic participation as a manifestation of civic responsibility.